Efektivitas Anestesi Dengan Penambah Ekstrak Daun Bandotan (Ageratum conyzoides L.) dalam Media Untuk Transportasi Basah Ikan Nila (Oreochromis niloticus) - -, Linayati -; Mardiana, Tri Yusufi; Syakirin, Muhammad Bahrus; Rifqi, Muhamad; Prayogo, Luhur Moekti; Yuniarti, Tristiana; Permatasari, Mahardhika Nur (Pena Akuatika : Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Bandotan leaves have the potential to be used as a natural anaesthetic for fish transportation. The objective of this study was to determine the effectiveness and optimal concentration of bandotan leaf extract (Ageratum conyzoides L.) on the survival of tilapia during wet transportation. This study employed a completely randomised design (CRD) with four treatments of bandotan leaf extract: P0 (Control), P1 (250 mg/3L), P2 (300 mg/3L), and P3 (350 mg/3L), each repeated three times. The test subjects were tilapia fingerlings transported in a wet transport system for 6 hours. The optimal dose of bendotan leaf extract was found to be P1 (250 mg/3L) with an induction time of 40 minutes, a recovery time of 5.5 hours, and a survival rate (SR) of 98.04±3.39%. Water quality during transport was within tolerable conditions for tilapia, with temperature ranging from 26–27.2 °C, pH from 7.43–7.66, and dissolved oxygen (DO) from 0.7–1.2 mg/L. Keywords: anaesthesia, bandotan leaves, tilapia, survival rate, wet transport